A Review on Gorgon Nut - Shankar, Mamta (International Journal of Pharmaceutical & Biological Archive, 2010)
Euryale ferox is the only species of the genus. It is commonly called Fox nut, Gorgon nut, Prickly water lily. The distribution of this species is now limited to the tropical and subtropical regions of south-east and East Asia. It has adapted to the tropical climate of India and is found in natural, wild forms in various parts of north-east India (Assam, Meghalya, and Orissa) and scattered pockets of central and northern India (eg. Gorakhpur and Alwar). However, Mithila (North Bihar) is the principal area of its present existence. Makhana is best grown in age- old perennial water bodies with a rich mucky bottom providing nutrients to the plants. Harvesting and processing of seed is still carried out by traditional methods. Makhana (Euryale ferox Salisb.) is one of the most common dry fruits utilized by the people due to low fat content, high contents of carbohydrates, protein and minerals. Both raw and fried Makhana are fairly rich in essential amino acids. Edible perisperm constitutes 80 per cent starch. Euryale ferox is a store house of macro- and micro-nutrients. The seeds are eaten raw or roasted. The seeds are sold in market and used as a farinaceous food.A lot of medicinal uses are recommended in the Indian and Chinese system of medicine. The different dietary components of the seeds were investigated to assess its nutritional significance.